Determinants of Budgeting Opportunistic Behavior - Ulla Ramadini; Sarwani; Lili Safrida (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The study attempted to determine and analyze the effect of (1) local revenue, (2) generalallocation funds, (3) special allocation funds, (4) profit-sharing funds, (5) excess differences inbudget calculations on opportunistic behavior government budget in Indonesia.This type of research is quantitative research. The researcher used secondary data. The population were all provinces in Indonesia during the research period 2014-2019. Based on the existing criteria, the sample size was 18 provinces. The data were tested using multiple linear regression. The results indicated that local revenue did not affect the opportunistic behavior of provincial government budgeting in Indonesia; general allocation funds did not affect the opportunistic behavior of provincial government budget formulation in Indonesia; special allocation funds affected the opportunistic behavior of provincial government budgeting inIndonesia; funds profit-sharing did not affect the opportunistic behavior of provincial government budget formulation in Indonesia; and the excess budget calculation did not affect the opportunistic behavior of provincial government budgeting in Indonesia. The further investigation with wider sample size was needed to clarify the finding.